„Człowiek z żelaza” Andrzeja Pągowskiego. Pozafilmowe życie plakatu - Bilecki, Arkadiusz (Załącznik Kulturoznawczy, 2024)
“A film about Solidarity”, as Man of Iron was briefly described, gained fame in Poland and international recognition. The film's promoters had to face the daunting task of saying something new about the film that had been well-known even before its premiere. Here was an acclaimed director taking on a subject that was famous all over the world: the birth of an official opposition movement in a country ruled by a communist dictatorship. The most suitable metaphor was created by Andrzej Pągowski, a young graphic designer experienced in working with film. He opted for religious associations which resonated particularly strongly in a society which, thanks to the Solidarity thaw, had become increasingly bolder in introducing Christian symbolism to the public space. Over the course of forty years, the poster has been subjected to numerous reinterpretations, some of which came from the author of the original.